Study the spread of resistant strains klebsiella Cephalosporins pattern of ESBL in Alassad University Hospital and in Tishreen University Hospital (Latakia University Journal -Medical Sciences Series, 2018)
This study was conducted to determine the prevalence of the spread of resistant strains klebsiella cephalosporins pattern of extended-spectrum beta lactamases ( ESBL). This study was conducted at the Laboratory of Microbiology at Assad University Hospital and at Tishreen University Hospital in Lattakia , and the combination of the resistance to cephalosporins with the resistance to other groups of antibiotics. A total of (200) isolates of klebsiella of different samples and different hospital departments, (150 ) sample of Assad university hospital (A), and (50) a sample of October hospital (B).A disc diffusion susceptibility test on the central models Mueller MH was conducted to determine the antimicrobial resistance patterns spectrum .ESBL screening was by double disc synergy test (DDST). Of the 200 isolates 54%( 108) were ESBL positive Resistance to penicillin and cephalosporins and gentamicin was significantly higher in ESBL isolates P< 0.001, indicating the combination of the resistance to these antibiotics with the existence of the ESBL. دراسة انتشار ذراري الكليبسيلة المقاومة للسيفالوسبورينات من النمط ESBL في مشفى الأسد الجامعي وفي مشفى تشرين الجامعي تهدف هذه الدراسة إلى تحديد معدل انتشار ذراري الكليبسيلة المقاومة للسيفالوسبورينات من النمط ESBL , أجريت هذه الدراسة في مخبر الأحياء الدقيقة في مشفى الأسد الجامعي وفي مشفى تشرين الجامعي باللاذقية, حيث تم جمع (200) عينة من جراثيم الكليبسيلة من مختلف العينات, ومن أقسام المشفى المختلفة , (150) عينة من مشفى الأسد الجامعي (A) و(50) عينة من مشفى تشرين (B). تم إجراء اختبار التحسس بطريقة الإنتشار على وسط موللر هنتون MH لتحديد نماذج المقاومة للصادات , كما تم استخدام اختبار القرص المضاعف التآزري ((DDST لتحديد الذراري من الكليبسيلة المفرزة لأنظيمات البيتالاكتاماز الواسعة الطيف .ESBLكان معدل انتشار جراثيم الكليبسيلة ايجابية ال ESBL (54% ) , بينت دراستنا ارتفاع نسب المقاومة للبنسلينات والسيفالوسبورينات والجنتامايسين عند هذه الجراثيم بالمقارنة مع الجراثيم من النوع نفسه وغير المفرزة لل ESBL .